PENGEMBANGAN BAHAN AJAR BERKARAKTER DIAGNOSA DAN REMEDIAL PEMBELAJARAN MATEMATIKA BERBASIS E-LEARNING UNTUK MENINGKATKAN ATTITUDE MAHASISWA - Rahmawati, Yeni; Fajarwati, Retno; Vahlia, Ira (JURNAL e-DuMath, 2018)
This study aims to develop teaching materials characterized by E-Learning. The subject of this research is the sixth semester student in the course of Diagnosis and Remedial Learning Mathematics. This research is a development research. Research method used: (1) information gathering, (2) planning, (3) product development, (4) initial test, (5) product revision, (6) field trial, (7) product revision. This resource can be used online and allows students to share frequently asked questions on Quipper School applications. The results of research in the form of teaching materials characterized based on E-Learning is valid and practical to improve student attitudes in learning.